Beyond Distinction: Theorising Cultural Evaluation as a Social Encounter. (June 2016) - Varriale, Simone
This article expands recent attempts to theorise the role of culture's materiality in Pierre Bourdieu's relational epistemology. Drawing on empirical research about the reception of rock and jazz in Italy, and focusing on the evaluative practices of Italian critics, the article theorises cultural evaluation as a social encounter between the dispositions of social actors (i.e. their habitus) and the aural, visual and narrative properties of cultural objects. The article argues that such encounters produce relational aesthetic experiences, which are neither a property of social actors (e.g. their class) nor of cultural artefacts, but emerge from interactions between the socio-historical specificity of the habitus and different cultural materials. This theoretical synthesis, it is argued, can account for meanings and affects which, albeit co-produced by embodied dispositions, are neither reducible to such dispositions nor to practices of distinction. Further, it can account for the formative power of aesthetic experiences, that is, the extent to which they create durable dispositions and attachments.